2008
DOI: 10.1080/17482620802042149
|View full text |Cite
|
Sign up to set email alerts
|

In the heat of the night, it is difficult to get it right—teenagers’ attitudes and values towards sexual risk-taking

Abstract: This study, using a hermeneutic approach, is based on data from four focus group interviews with 25 Swedish teenagers participating, ranging from 18Á19 years of age. The aim is to gain a deeper understanding of teenagers' values and attitudes towards sexually transmitted infections (STIs) and sexual risk-taking. The teenagers seem to seek an excuse to fend off responsibility and deny their sexual risk-taking, an excuse provided by drunkenness. Under the influence of alcohol, teenagers are not too shy to have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The intervention increased knowledge and improved student attitudes and behaviors regarding condom use more than standard education. Several studies have shown that youths, despite feeling they have sufficient knowledge on STIs and unwanted pregnancies, do not use protection (Christianson et al, 2003;Darj & Bondestam, 2003;Hammarlund et al, 2008;Higgins & Wang, 2015;Häggstrom-Nordin et al, 2002;Larsson et al, 2006), but that changed attitudes to condom use alter behaviors (Häggstrom-Nordin et al, 2002;Larsson et al, 2006). This shows that SAFETY can be a beneficial supplement to standard sex education and is more effective with regard to knowledge of condom use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention increased knowledge and improved student attitudes and behaviors regarding condom use more than standard education. Several studies have shown that youths, despite feeling they have sufficient knowledge on STIs and unwanted pregnancies, do not use protection (Christianson et al, 2003;Darj & Bondestam, 2003;Hammarlund et al, 2008;Higgins & Wang, 2015;Häggstrom-Nordin et al, 2002;Larsson et al, 2006), but that changed attitudes to condom use alter behaviors (Häggstrom-Nordin et al, 2002;Larsson et al, 2006). This shows that SAFETY can be a beneficial supplement to standard sex education and is more effective with regard to knowledge of condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that youths' difficulties in communicating with partners contribute to failure in using condoms. The dialogue on responsibility for sexual health was seen by youths as more intimate than the act of intercourse or putting on a condom (Hammarlund et al, 2008). Another study (Darj & Bondestam, 2003) has found that one reason condoms are not used is that it is unclear whose responsibility it is to mention condoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the interpretive work, the researchers came to understand how and why a positive integration in Swedish society also meant a safe and secure experience of Swedish healthcare. In a study of teenagers' sexual risk-taking and experiences of HPV (human papillomavirus) a virulent sexually transmitted disease, Hammarlund et al (2008) found a fairly easy-going attitude until a venereal disease occurred.…”
Section: Lifeworld Hermeneuticsmentioning
confidence: 99%
“…2012;Kuperberg in Padgett 2017). Mladostniki pod vplivom alkohola niso imeli zadržkov pred priložnostnim spolnim odnosom, hkrati pa jim je pogovor o uporabi kondoma pov-zročal nelagodje, zato so se mu raje izognili (Hammarlund, Lundgren in Nyström 2008). Arielle Kuperberg in Padgett (2017) sta ugotovila, da je tvegano spolno vedenje pogostejše v situacijah, ki jih določajo skripti zabavanja in prekomernega pitja.…”
Section: Skripti Priložnostnih Spolnih Odnosov Uživanje Psihoaktivnih...unclassified